THE INFLUENCE OF ANIMATED MEDIA ON SCIENCE LEARNING OUTCOMES OF PRIMARY SCHOOL STUDENTS (LIBRARY RESEARCH) - Winny Sunfriska Limbong, Robinson Hutagaol, Nanda Ayu Setiawati, Rachel Yuni Erika Simanjuntak (Education Achievement: Journal of Science and Research, 2020)
The purpose of this study is to determine the effect of animation media on science learning outcomes of elementary school students. This study is qualitative with library research methods. The data sources used in this study were secondary data that were relevant to the study. The data analysis technique used was qualitative data analysis. The data was analyzed by using Miles and Huberman theory with three stages, consisted of: Data Collection, Data Reduction and Drawing Conclusions. Based on the analysis of the data obtained, it can be concluded that animation media affected on science learning outcomes of elementary school students. From the analysis of the data, animation media has a positive influence on science learning outcomes, teachers must understand the learning steps of anima- tion media on learning process.